Pengaruh Kinerja Pegawai Pegawai terhadap Pengembangan Karir Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Karawang - R, Yurri A; Solehudin, Solehudin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of employee performance on the career development of the Public Works Service and Karawang regency spatial planning. This type of research is quantitative research with descriptive and verification research methods. The sample in this study was 175. The sampling technique used in this study was saturated sampling. The analysis model in this study uses a multiple linear regression analysis model. The results of the study show that there is an influence between employee performance on the career development of the Public Works Office and spatial planning of the Karawang regency. Keywords: Competency, Employee Performance